Indigenous women of Chiapas, Mexico: public policies with a gender and rights approach - Cruz Solís, Imelda (2022)
This article presents the research advances of the perception that indigenous women have about the actions that the Mexican State has implemented through public policies with a focus on human rights and gender. This approach poses the challenge of addressing the issues faced by women and men, respecting their dignity as individuals and promoting gender equity. The inclusion of women in public activities has undergone modifications that have allowed them to insert themselves in different spaces. In this sense, even though different actions have been carried out by the government for the insertion of women on equal terms, at present we find that the participation of women is not proportional or does not correspond to respect for their rights, for example, in the reduction of inequalities due to their gender status and the reduction of violence. That is, although they could have greater purchasing power and participation, this does not change their situation of vulnerability, deepening when talking about the indigenous population. The analysis methodology is from the qualitative approach. Through a non-probabilistic sampling, biographical narratives were constructed through the application of in-depth interviews with 15 indigenous women from Chiapas, Mexico and 5 advisors of organizational and productive processes in different municipalities of the Altos de Chiapas region. The main conclusion of this work is that important advances have been observed in theoretical discussions and in the legal field to establish laws, norms and guidelines at the international, national and local levels, but in daily life indigenous women in Chiapas, Mexico, perceive little recognition of their rights.